Hydrological Characteristics Assessment of Jalaur River System and Its Bottom Sediments, Province of Iloilo, Panay Island - Golez, Nelson V.; Borlongan, Ilda G.; Lorque, Felizardo (Silliman Journal, 2022)
Rivers are important to civilization because river water can be diverted for agricultural irrigation, industry, hygiene, and related uses. Most rivers have varied hydrological characteristics like water EFQUI nPXSBUFBOEWPMVNFEJTDIBSHFTXIFONFBTVSFEEVSJOHUIF wet and dry season. In addition, rivers do carry dissolved minerals and organic compounds. A hydrologic monitoring was done in strategic sampling points along the river to cover the upstream #BOCBO 1FRVF×P BMJOPH NJETUSFBN .PSPCPSP %JOHMF XJUI TVCQPJOUT CFGPSF BOE BGUFS UIF EBN *NCBOH 1FRVF×POFBS Passi Sugar Central and Licuan, Dingle next to the National Power Corporation) and downstream (Nabitasan, Leganes) sections of the Jalaur River. Sampling was done three times per season (dry BOEXFUTFBTPOT BUFBDIPGUIFmWFTBNQMJOHTJUFT 8BUFSMFWFMBOEnPXSBUFWBSJBUJPOTXFSFPCTFSWFEEVSJOHUIF occurrence of a tropical storm and torrential rains brought by a typhoon. Depth ranges from 0.45 meters (dry season) to 6.0 meters (wet season). The river current in the upstream station was greater than the mid and downstream stations at a rate of 2.5, 0.22 and 0.33 m/sec in the wet season and 0.37, 0.2 and 0.08m/sec in the dry season, respectively. River discharges were also higher (108.5, 41.04, and 19.99 m3/sec) during the wet season than in the dry season (3.89, 29.40, and 28.08 m3/sec) for the upper, middle, and downstream stations. Water transparency during the wet season ranged from 5-15 cm whereas 31-55 cm was recorded during the dry season. Color of the water changed from murky brown to brown during the wet season and from clear to light green during the dry months from Calinog down to Leganes except in Imbang, 1FRVF×P4BO&OSJRVFTJUFXJUIWFSZVOEFTJSBCMFDPMPS CMBDLBOE odor (ammoniacal) during dry months (milling season). Highest precipitation of 317.24 mm in the wet season and barely 5.2 mm during the dry season was recorded. Bottom sediments were found to be sand to sandy loam, to silty loam from upstream to downstream, respectively. Soil pH was neutral to slightly basic (7.10-8.17). Available phosphorus measurements were higher (11.22-30.50 ppm P) in soils from Calinog to Leganes while the amount of available iron (Fe) increased as the concentration of acetate soluble sulfate decreased, except in Moroboro, Dingle and Nabitasan, Leganes that showed an abnormal increase twice the initial value. The organic matter content of the sediments taken from all sampling sites yielded a wide range of 1.31—4.53 % that decreased to 0.04 from 2.46 % in all sampling sites from wet to dry season. Highest value was in the midstream with values ranging from 4.53—2.46 %. The results of this study show that sediment agitation by recreational activity and storm surges associated with the dryDPMETFBTPOBSFSFTQPOTJCMFGPSUIFJNQBDUPOXBUFSRVBMJUZBOE not recreational users directly. This implies that a follow up study and continuous monitoring is needed to ensure the safety of all end users of the river system, otherwise its use in the future will CFMJNJUFEUPRVBSSZJOHPGDPODSFUJOHBOEFNCBOLNFOUNBUFSJBMT for civil work projects.